Genome-wide identification and characterization of NPF family reveals NtNPF6.13 involving in salt stress in Nicotiana tabacum - Zhang, Hui; Li, Zefeng; Xu, Guoyun; Bai, Ge; Zhang, Peipei; Zhai, Niu; Zheng, Qingxia; Chen, Qiansi; Liu, Pingping; Jin, Lifeng; Zhou, Huina (Frontiers in Plant Science, 2022)
Proteins of the Nitrate Transporter 1 /Peptide Transporter (NPF) family transport a diverse variety of substrates, such as nitrate, peptides, hormones and chloride. In this study, a systematic analysis of the tobacco (Nicotiana tabacum) NPF family was performed in the cultivated ‘K326’. In total, 143 NtNPF genes were identified and phylogenetically classified into eight subfamilies, NPF1 to NPF8, based on the classification of NPF families in other plant species. The chromosomal locations and structures of the NtNPF genes were analyzed. To explore the function of NtNPF genes in chloride uptake or transpor, the expression profiles of NtNPF genes under salt stress were examined by RNA-sequencing. Most NtNPF6 genes responded to salt stress in the roots and leaves. The expression of NtNPF6.13 was significantly down-regulated after salt stress for 12 h. The chloride content was reduced in the roots of ntnpf6.13 mutant. These findings support the participation of NtNPF6.13 in chloride uptake. Several other NtNPF genes that play potential roles in chloride metabolism of tobacco require further study.